Laços Sociais: por uma epistemología da hospitalidade [Social ties: towards an epistemology of hospitality - Korstanje, Maximiliano Emanuel (PASOS Revista de Turismo y Patrimonio Cultural, 2016)
Thinking this contemporary world invites to discuss the role of mobilities and tourism in the global geography. In so doing, as Korstanje puts it, the contours between centre and periphery not only blur, but also ignite conflict, uncertainness and violence. This is the reason why hospitality plays a crucial role in revitalizing the social ties, some of them weakened by tourism meetings (Korstanje & Skoll, 2014; Korstanje & Olsen 2011; Korstanje, 2015). The present book, edited y Marcia Capellano Dos Santos & Isabel Baptista contain 15 excellent chapters divided in two sides. The part one is based on a collection of manuscripts authored by Brazilian authors, while the second offers the viewpoint of Portuguese writers